Khushoo In Salah: An Overview of Nafs (Islamic Psychological Perspective) - Wahyu Rahmanto, Septian; Fachrunisa, Rahma Ayuningtyas; Suseno, Bayu (Universitas Muhammadiyah Surakarta, 2024)
Worship practices have been found to contribute to mental health. Salah is an obligatory act of worship and has priority in Islam. The benefits of salah services are also studied about the movements carried out in salah. Even though the movements of salah can be seen, not all Muslims can do it well because of the lack of humility or solemnity in salah. This research aims to explain the dynamics of khushoo from the perspective of nafs from an Islamic psychology perspective and how to achieve a state of khushoo in salah. This research uses a literature review method from various scientific articles and books about khushoo. The research results show that khushoo is related to the mental stages of nafs al ammarah, nafs al lawwamah, and nafs al mutmainah. Further discussion regarding the dynamics of khushoo in the review salah of the three nafs is also discussed in this article. Several strategies for achieving khushoo in salah are briefly reviewed.